Pengaruh Electronic Word Of Mouth (eWOM) Terhadap Keputusan Pembelian Produk Esteh Indonesia - Alawiyah, Nanik; Farmayanti, Narni; Gita Dewi, Triana (Forum Agribisnis, 2025)
Nowadays, many consumers search and compare reviews online before making a purchase decision, including accessing information from @FOODFESS2. By sharing information on @FOODFESS2 via Twitter, consumers can easily find reviews of various foods and beverages, including Esteh Indonesia products. Electronic Word of Mouth (eWOM) information disseminated by Autobase members on @FOODFESS2 is very effective in influencing consumer decisions to buy Esteh Indonesia products. This study aims to analyze the influence of electronic Word of Mouth (eWOM) on purchasing decisions for Esteh Indonesia products. Data analysis uses descriptive analysis and SEM-PLS analysis. The results of SEM-PLS analysis show that the dimension of positive emotional expression has a significant influence on purchasing decisions for Esteh Indonesia products. Meanwhile, Esteh Indonesia's purchasing decision was not significantly influenced by the dimensions of platform assistance, concern for other customers, release of negative emotions and asking for advice. Based on the results of this survey, Esteh Indonesia is motivated to continue to improve product quality, improve customer service, continue to invite consumers to share their positive experiences and collect customer experiences so that consumers can share their positive experiences with Esteh Indonesia.